Cyclic peptide unguisin A is an anion receptor with high affinity for phosphate and pyrophosphate. Issue 14 (15th March 2017) - Daryl Ariawan, A.; Webb, James E. A.; Howe, Ethan N. W.; Gale, Philip A.; Thordarson, Pall; Hunter, Luke
Abstract : Unguisin A (1 ) is a marine-derived, GABA-containing cyclic heptapeptide with a high binding affinity for phosphates. Abstract : Unguisin A (1 ) is a marine-derived, GABA-containing cyclic heptapeptide. The biological function of this flexible macrocycle is obscure. Here we show that compound1 lacks any detectable activity in antimicrobial growth inhibition assays, a result that runs contrary to a previous report. However, we find that1 functions as a promiscuous host molecule in a variety of anion-binding interactions, with high affinity particularly for phosphate and pyrophosphate. We also show that a series of rigidified, backbone-fluorinated analogues of1 displays altered affinity for chloride ions.